2018
DOI: 10.1007/s00167-018-5075-3
|View full text |Cite
|
Sign up to set email alerts
|

3D strain in native medial meniscus is comparable to medial meniscus allograft transplant

Abstract: These results suggest that time zero MAT performs in a similar manner to the native meniscus. Optimizing MAT strain behavior may lead to potential improvements in its chondroprotective effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…11,39 However, sonography, which is a less invasive method, may provide promising information about meniscus extrusion during weight bearing. 40,41 In our study, it was observed that meniscal extrusion did not exhibit a statistically significant increase and was not higher than 3 mm during follow-up (2.27 vs. 2.98, 2.64 and 2.39). Therefore, it can be suggested that the combination of CBMA injection and surgical technique provides better meniscocapsular healing and provides lower rates of extrusion.…”
Section: Discussionmentioning
confidence: 44%
“…11,39 However, sonography, which is a less invasive method, may provide promising information about meniscus extrusion during weight bearing. 40,41 In our study, it was observed that meniscal extrusion did not exhibit a statistically significant increase and was not higher than 3 mm during follow-up (2.27 vs. 2.98, 2.64 and 2.39). Therefore, it can be suggested that the combination of CBMA injection and surgical technique provides better meniscocapsular healing and provides lower rates of extrusion.…”
Section: Discussionmentioning
confidence: 44%
“…Accurate positioning of a meniscal allograft is thought to be an important factor for successful outcomes after MAT. 14 , 23 The nonanatomic graft position can cause disadvantages in knee biomechanics. In particular, when the graft position is >5 mm away from the native meniscus, it can affect the contact pressure and adversely affect the cartilage prevention ability of the graft.…”
Section: Discussionmentioning
confidence: 99%
“…In the bone plug method, proper meniscal size and exact visualization of the native meniscal insertion is a key factor for the chondroprotective effect, but passing the graft through a tight medial joint with a cylindrical bone plug can be difficult. 9 , 14 These different surgical techniques may lead to different results, including meniscal extrusion, meniscal tear, progression of degenerative change, and clinical outcomes. 18 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are limited human data regarding the strain pattern and distribution after MAT; however, one study did use advanced 3-dimensional imaging to evaluate the strain placed on the meniscus, both for the native and transplanted meniscus. They found no significant difference in the total strain or the regional strain distribution between the native meniscus and allograft 33 . In addition, when nonirradiated allografts were assessed in rabbits 6 months after transplantation using indentation testing, there were no significant differences between the nonoperative contralateral meniscus and the transplanted one 34 .…”
Section: Biomechanics After Transplantmentioning
confidence: 93%